Associations of Pre-Diagnostic Serum Levels of Total Bilirubin and Albumin With Lung Cancer Risk: Results From the Southern Community Cohort Study - Hyung-Suk Yoon; Xiao-Ou Shu; Chris Shidal; Jie Wu; William J. Blot; Wei Zheng; Qiuyin Cai (Frontiers in Oncology, 2022)
BackgroundPrevious studies conducted among European and Asian decedents reported inverse associations of serum total bilirubin and albumin with lung cancer risk. Yet, no study has been conducted among African Americans or low-income European Americans.MethodsThis study included 522 incident lung cancer cases and 979 matched controls nested in the Southern Community Cohort Study, a cohort of predominantly low-income African and European Americans. Serum levels of total bilirubin and albumin, collected up to 11 years prior to case diagnoses, were measured by a clinical chemistry analyzer. Conditional logistic regression models were applied to evaluate the associations of total bilirubin and albumin with lung cancer risk.ResultsOverall, serum levels of total bilirubin (ORT3 vs. T1 = 0.96, 95% CI: 0.66-1.39) were not significantly associated with lung cancer risk. However, higher levels of serum total bilirubin were significantly associated with decreased risk of lung cancer among participants who were diagnosed within two years following sample collection (ORT3 vs. T1 = 0.36, 95% CI: 0.15-0.87) and among former/never smokers (ORT3 vs. T1 = 0.54, 95% CI: 0.32-0.93). Serum levels of albumin were significantly associated with decreased risk of lung cancer overall (ORT3 vs. T1 = 0.70, 95% CI: 0.50-0.98) and among African Americans (ORT3 vs. T1 = 0.62, 95% CI: 0.41-0.96), but not among European Americans.ConclusionOur results indicate that in a low-income African American and European American population, serum levels of total bilirubin may be related to lung cancer progression and differ by smoking status. Meanwhile, the association of serum albumin levels with lung cancer risk may differ by race. Further studies are warranted to confirm these results.